KEPENTINGAN REPUBLIK RAKYAT TIONGKOK MENERAPKAN BELT AND ROAD INITIATIVE (BRI) DI MALAYSIA (2013 – 2017) - Mahotama Jaya, Ngurah Gede; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A. A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research describes China’s interest related to BRI initiative and its implementation in Malaysia. BRI has developed lanes which comprise into land and maritime lane. Southeast Asia is included in maritime pathway which has an important geographical, historical and strategic position towards China’s national interest in seeking partnership with one of the countries in the region, namely Malaysia. However, the international situation surrounding Malaysia has also give an impression that Chinese policies utilize BRI’s initiative to benefit its own interest rather than Malaysia interests including the South China Sea issue. Not to mention the Malacca Strait has created a dilemma towards China so that BRI is seen as a solution to overcome it. This research utilizes qualitative methods with secondary sources which then analyzed using the concept of National Interest and China’s Grand Strategy, the data were collected from books, journals, websites, etc.   Keywords: Belt and Road Initiative (BRI), National Interest, Grand Strategy